Cardiorespiratory fitness as a predictor of intestinal microbial diversity and distinct metagenomic functions. Issue 1 (December 2016) - Estaki, Mehrbod; Pither, Jason; Baumeister, Peter; Little, Jonathan; Gill, Sandeep; Ghosh, Sanjoy; Ahmadi-Vand, Zahra; Marsden, Katelyn; Gibson, Deanna
Abstract Background Reduced microbial diversity in human intestines has been implicated in various conditions such as diabetes, colorectal cancer, and inflammatory bowel disease. The role of physical fitness in the context of human intestinal microbiota is currently not known. We used high-throughput sequencing to analyze fecal microbiota of 39 healthy participants with similar age, BMI, and diets but with varying cardiorespiratory fitness levels. Fecal short-chain fatty acids were analyzed using gas chromatography. Results We showed that peak oxygen uptake (VO2 peak), the gold standard measure of cardiorespiratory fitness, can account for more than 20 % of the variation in taxonomic richness, after accounting for all other factors, including diet. While VO2 peak did not explain variation in beta diversity, it did play a significant role in explaining variation in the microbiomes' predicted metagenomic functions, aligning positively with genes related to bacterial chemotaxis, motility, and fatty acid biosynthesis. These predicted functions were supported by measured increases in production of fecal butyrate, a short-chain fatty acid associated with improved gut health, amongst physically fit participants. We also identified increased abundances of key butyrate-producing taxa (Clostridiales, Roseburia, Lachnospiraceae, andErysipelotrichaceae ) amongst these individuals, which likely contributed to the observed increases in butyrate levels. Conclusions Results from this study show that cardiorespiratory fitness is correlated with increased microbial diversity in healthy humans and that the associated changes are anchored around a set of functional cores rather than specific taxa. The microbial profiles of fit individuals favor the production of butyrate. As increased microbiota diversity and butyrate production is associated with overall host health, our findings warrant the use of exercise prescription as an adjuvant therapy in combating dysbiosis-associated diseases.